Knowledge of nurse educators working in higher education regarding the “Undetectable = Untransmissible” concept in HIV care: A scoping review - Foromo, Robert Muraga; Mulaudzi, Mavis; Nyandeni, Sinethemba (Orapuh Journal, 2025)
IntroductionThe Undetectable = Untransmissible (U=U) concept, which emphasises sustained HIV viral suppression through effective antiretroviral therapy, has gained global acceptance. However, awareness and understanding of U=U among nurse educators, particularly within academic healthcare institutions, remain limited. This study aims to assess nurse educators’ understanding of HIV, specifically in relation to the U=U concept, within academic healthcare settings.PurposeThis scoping review aimed to evaluate the current knowledge of nurse educators working in higher education regarding the U=U concept in HIV care.MethodsA comprehensive literature search was conducted using English-language keywords across multiple databases, including PubMed, Scopus, Web of Science, EBSCOhost, and ProQuest. The search focused on publications published between January 2010 and April 2025. The review followed the Arksey and O’Malley framework and adhered to PRISMA-ScR guidelines.ResultsA total of 38 articles were identified as potentially eligible for inclusion. However, 30 were excluded after full-text screening for reasons such as incorrect topic, setting, outcome, population, or publication year. Consequently, eight articles met the inclusion criteria. Four major themes emerged: curriculum development and implementation; knowledge and beliefs about U=U; communication barriers; and strategies for improvement.ConclusionAcademic healthcare institutions should empower nurse educators with structured training programmes on HIV-related topics, enabling them to educate students effectively and help reduce new infections and stigma. This review highlights barriers to implementation and identifies effective strategies for enhancing U=U education in nursing, bridging the gap between policy and practical application.